A precise study on effects that trigger alkaline hemicellulose extraction efficiency. (August 2016) - Hutterer, Christian; Schild, Gabriele; Potthast, Antje
Highlights: Alkaline hemicellulose extraction efficiency of hardwood paper pulps. Xylan degradation in cold caustic extractions using synthetic white liquor. Uniformity and purity of alkaline extracted hardwood hemicelluloses. Abstract: The conversion of paper-grade pulps into dissolving pulps requires efficient strategies and process steps to remove low-molecular noncellulosic macromolecules generally known as hemicelluloses. Current strategies include alkaline extractions and enzymatic treatments. This study focused on the evaluation of extraction efficiencies in alkaline extractions of three economically interesting hardwood species: beech ( Fagus sylvatica ), birch ( Betula papyrifera ), and eucalyptus ( Eucalyptus globulus ). Substrate pulps were subjected to alkaline treatments at different temperatures and alkalinities using white liquor as the alkali source, followed by analyses of both pulps and hemicellulose-containing extraction lyes. The extracted hardwood xylans have strong potential as an ingredient in the food and pharmaceutical industries. Subsequent analyses revealed strong dependencies of the extraction efficiencies and molar mass distributions of hemicelluloses on the process variables of temperature and effective alkalinity. The hemicellulose content of the initial pulps, the hardwood species, and the type of applied base played minor roles.